2021
DOI: 10.3389/fonc.2021.710248
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Based Radiomics for Preoperative Prediction of Tumor Deposits in Rectal Cancer

Abstract: ObjectiveTo develop and validate a computed tomography (CT)-based radiomics model for predicting tumor deposits (TDs) preoperatively in patients with rectal cancer (RC).MethodsThis retrospective study enrolled 254 patients with pathologically confirmed RC between December 2017 and December 2019. Patients were divided into a training set (n = 203) and a validation set (n = 51). A large number of radiomics features were extracted from the portal venous phase images of CT. After selecting features with L1-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…According to the current European Society for Medical Oncology (ESMO) preoperative risk assessment criteria, patients with TDs are classified into a high-risk group with a worse prognosis ( 9 ). A previous study confirmed that the presence of TDs is an independent risk factor for the prognosis of patients with RC ( 10 ). An analysis of two prognostic studies in N0 and N1c stages showed a significant difference in the five-year survival rates (N0, 91.5%; N1c, 37%) ( 11 ).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…According to the current European Society for Medical Oncology (ESMO) preoperative risk assessment criteria, patients with TDs are classified into a high-risk group with a worse prognosis ( 9 ). A previous study confirmed that the presence of TDs is an independent risk factor for the prognosis of patients with RC ( 10 ). An analysis of two prognostic studies in N0 and N1c stages showed a significant difference in the five-year survival rates (N0, 91.5%; N1c, 37%) ( 11 ).…”
Section: Introductionsupporting
confidence: 58%
“…Meanwhile, artificial intelligence including deep neural networks has demonstrated high performance in the analysis of medical images ( 21 23 ), providing cancer risk assessment, recurrence, and survival predictions with higher accuracy than human experts. Recently, several radiomic models have been developed based on ultrasound (US), computed tomography (CT), and MRI to preoperatively predict TDs in patients with RC ( 10 , 24 , 25 ). However, the sample sizes in these studies were relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the radiomics model allowed quantitative features to be extracted from CT images and subtle patterns that might be overlooked by human observers to be captured, while the clinical model provided additional demographic and clinical information. We also applied deep learning to predict the presence of OLNM in cT1-2N0 patients ( Jin et al, 2021 ). The deep learning model based on ResNet50 can directly analyze raw medical images and learn complex and high-level representations of the data ( Yu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that T2WI-based radiomics from the intratumoral region could predict ENE with an AUC of 0.612. Jin et al and Chen et al reported that radiomics features obtained from intratumoral and peritumoral fat were used to construct a model for predicting tumor deposits [ 16 , 32 ]. These studies found that the combined model incorporating intratumoral and peritumoral fat and clinical factors provided good performance for predicting tumor deposits.…”
Section: Discussionmentioning
confidence: 99%